Hubungan antara dispersi qt pasca bedah pintas arteri koroner dengan kejadian kardiovaskular mayor - Reynold Agustinus; Yoga Yuniadi; Budhi Setianto (The Indonesian Heart Association, 2010)
Introduction:Coronary artery bypass graft (CABG) improves prognosis in patient with coronary artery disease. However, some patients might experi-ence major adverse cardiovascular events. An increase in QT dispersion is predictor of sudden cardiac death and associated with an increased risk of major adverse cardiovascular events (MACE) after successful percutaneous coronary intervention in patients with acute myocardial infarction. This study was aimed to evaluate the correlation between QT dispersion and MACE after isolated CABG.Methods: This was a retrospective cohort study of post-CABG patients using medical record analysis in National Cardiovascular Center Harapan Kita Jakarta during period of January until December 2007 with 1 year fol-low up. QT dispersion was defined as difference between the longest and the shortest QT interval of standard 12-lead ECG on the fifth or the seventh post operative day. It was assessed manually and blinded to clinical data then divided into two groups (QT d <60 and QT d > 60).Results: Of 517 patients who had undergone isolated CABG, 343 were eligible to be analyzed. There are 303 men and 40 women (mean age 58,0 ± 7,9 years) with mean QT dispersion 55,7 ± 19,9 ms. The incidences of MACE were 43 (12.5%) comprised with 19 (5,5%) heart failure, 11 (3,2%) non fatal acute coronary syndrome, 2 (0,6%) stroke and 11 (3,2%) subject died due to cardiac or non cardiac caused. QT dispersion > 60 ms related with total MACE (RR 3.58; [95 % CI 1.93 – 6.65], p< 0.01), non fatal acute coronary syndrome (RR 9.41 [95% CI 2,03 – 43,58], p = 0.004) and acute heart failure (RR 4.56 (95% CI 1.73 – 12.00, p = 0.002).Conclusion: QT dispersion > 60 ms in subject undergone isolated CABG had increased risk of total MACE, acute heart failure, and non fatal acute coronary syndrome during 1 year follow up.